PENERAPAN MODEL PEMBELAJARAN TERBALIK (RECIPROCAL TEACHING) UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI MIA 6 SMAN 1 PEKANBARU - Stifany, Aldilla; ', Herdini; Linda, Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Implementation of Reciprocal Teaching model to improve student activity and learning mastery of solubility and solubility product in class XI MIA 6 SMAN 1 Pekanbaru has been conducted. The student activities that corrected were embrace, ask question, done the exercises and group discussion. The improvement of students learning activities implies an increase in mastery learning students. The subject of this research were 27 students that involved conducted in two cycles of learning. Each cycle consisted of two meetings through four stages, they are planning, action, observation, and reflection. The data of this research was collected by using observation sheet and test. The result showed that student activity was increased and achieved the standard criteria. The student activity at the first cycle was 49,64% and at the second cycle was 63,76% with good criteria. It was found out that there was improvement in students Learning Mastery and the standard criteria was achieved. The first and the second cycle average percentage of learning mastery were 70,37% and 85,18% respectively. Based on the result, was concluded that application of Reciprocal Teaching model can improve student activity and learning mastery.Keyword : Reciprocal Teaching, Student Activities, Learning Mastery Student